Correlation Of Body Mass Index With Prostate Volume In Benign Prostatic Hyperplasia Patients - Tritanto, Rio; Arifin, Fransiscus; Prajitno, Subur (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Benign prostatic hyperplasia (BPH) is the most common prostatic disease inmen. Multiple factors influence the pathogenesis of BPH, and one of them is obesity. Variousstudies about the correlation between obesity and prostate volume show inconsistent results.Some studies reported that obesity correlates with prostate volume, whereas others didn't findthe correlation between obesity and prostate volume. Therefore, this study aims to find thecorrelation between obesity and prostate volume. Purpose: To find the relationship between body mass index (BMI) and BPH patients'prostate volume. Methods: BMI was measured by BMI formula, and prostate volume was measured bytransabdominal ultrasound (TAUS). This study was conducted in RSUD Ibnu SinaKabupaten Gresik by looking at medical records in January 2016-September 2017. This studywas an analytical observational study with a cross-sectional approach. This study uses LinearRegression Test to analyze the correlation of in-between variables. This study's populationwas patients with a diagnosis of BPH that undergo hospitalization in RSUD Ibnu Sina (273medical records). The study sample that corresponding to inclusion and exclusion criteria are27 medical records. Result: The average prostate volume in underweight criteria was 44,5 cm3, in normal criteriais 42,4 cm3. Highest average of prostate volume found in overweight criteria, which was 64,3cm3. In the obese criteria, the average prostate volume was 32,2 cm3. The average prostatevolume was 46,0 cm3. From the linear regression test, we found the value of p=0,881 andR2=0,01. Conclusion: There is no significant correlation between BMI and prostate volume in thisstudy